Correlates of human papillomavirus (HPV) vaccination initiation and completion among 18-26 year olds in the United States - Eric Adjei Boakye; Daphne Lew; Meera Muthukrishnan; Betelihem B. Tobo; Rebecca L. Rohde; Mark A. Varvares; Nosayaba Osazuwa-Peters (Taylor & Francis Group, 2018)
Purpose: To examine correlates of HPV vaccination uptake in a nationally representative sample of 18-26-year-old adults. Methods: Young adults aged 18-26 years were identified from the 2014 and 2015 National Health Interview Survey (n = 7588). Survey-weighted multivariable logistic regression models estimated sociodemographic factors associated with HPV vaccine initiation (≥1 dose) and completion (≥3 doses). Results: Approximately 27% of study participants had initiated the HPV vaccine and 16% had completed the HPV vaccine. Participants were less likely to initiate the vaccine if they were men [(adjusted odds ratio) 0.19; (95% confidence interval) 0.16-0.23], had a high school diploma (0.40; 0.31-0.52) or less (0.46; 0.32-0.64) vs. college graduates, and were born outside the United States (0.52; 0.40-0.69). But, participants were more likely to initiate the HPV vaccine if they visited the doctor's office 1-5 times (2.09; 1.56-2.81), or ≥ 6 times (1.86; 1.48-2.34) within the last 12 months vs. no visits. Odds of completing HPV vaccine uptake followed the same pattern as initiation. And after stratifying the study population by gender and foreign-born status, these variables remained statistically significant. Conclusions: In our nationally representative study, only one out of six 18-26 year olds completed the required vaccine doses. Men, individuals with high school or less education, and those born outside the United States were less likely to initiate and complete the HPV vaccination. Our findings suggest that it may be useful to develop targeted interventions to promote HPV vaccination among those in the catch-up age range.